Cell Membrane Fatty Acid Composition of Chryseobacterium frigidisoli PB4T, Isolated from Antarctic Glacier Forefield Soils, in Response to Changing Temperature and pH Conditions - Bajerski, Felizitas; Wagner, Dirk; Mangelsdorf, Kai (Frontiers in Microbiology, 2017)
Microorganisms in Antarctic glacier forefields are directly exposed to the hostile environment of their habitat characterized by extremely low temperatures and changing geochemical conditions. To survive under those stress conditions microorganisms adapt, among others, their cell membrane fatty acid inventory. However, only little is known about the adaptation potential of microorganisms from Antarctic soil environments. In this study, we examined the adaptation of the cell membrane polar lipid fatty acid inventory of Chryseobacterium frigidisoli PB4T in response to changing temperature (0 °C to 20 °C) and pH (5.5 to 8.5) regimes, because this new strain isolated from an Antarctic glacier forefield showed specific adaptation mechanisms during its detailed physiological characterization. Flavobacteriaceae including Chryseobacteria occur frequently in extreme habitats such as ice-free oases in Antarctica. C. frigidisoli shows a complex restructuring of membrane derived fatty acids in response to different stress levels. Thus, from 20 °C to 10 °C a change from less iso-C15:0 to more iso-C17:1ω7 is observed. Below 10°C temperature adaptation is regulated by a constant increase of anteiso-FAs and decrease of iso-FAs. An anteiso and bis-unsaturated fatty acid, anteiso-heptadeca-9,13-dienoic acid, shows a continuous increase with decreasing cultivation temperatures underlining the particular importance of this fatty acid for temperature adaptation in C. frigidisoli. Concerning adaptation to changing pH conditions, most of the dominant fatty acids reveal constant relative proportions around neutral pH (pH 6-8). Strong variations are mainly observed at the pH extremes (pH 5.5 and 8.5). At high pH short chain saturated iso- and anteiso-FAs increase while longer chain unsaturated iso- and anteiso-FAs decrease. At low pH the opposite trend is observed. The study shows a complex interplay of different membrane components and provides, therefore, deep insights into adaptation strategies of microorganisms from extreme habitats to changing environmental conditions.